KEMAMPUAN HASIL BELAJAR PADA PROSES PEMBELAJARAN BIOLOGI MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS INKUIRI TERHADAP SISWA SMA - Habibah Nuhayati; Muhammad Zaini; Aulia Ajizah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
Learning invertebrate sub concepts at Muhammadiyah 2 High School in Banjarmasin still uses conceptual learning. This causes students not to have the ability to learn in scientific activities. My research for learning effectiveness uses inquiry-based learning models for product cognitive learning outcomes, cognitive learning outcomes of the process. The method used is quasi-experimental and descriptive. Samples were taken in three classes from 3 classes (Class X-A, X-B, and X-C). Data collection techniques used covariance analysis. The results showed (1) the application of effective inquiry-based learning models to the cognitive learning outcomes of the product. The results of the study showed that product learning research was significant between the treatment classes and the control class (F = 22.11; P = 0.0001). (2) the application of effective inquiry-based learning models to the learning outcomes of cognitive processes. In the cognitive learning process there was a significant difference between the control class and the control class (F = 18.16; P = 0,0001).